FOMO dalam Komunitas Lari: Studi Fenomenologi tentang Motivasi Peserta Event Lari Virtual di Era Pasca-Pandemi - Riu, Isma Azis (PT Maju Malaqbi Makkarana, 2025)
Fear of Missing Out (FOMO) has become a significant psychosocial phenomenon in the virtual running community in the post-pandemic era. This qualitative phenomenological study aims to explore the role of FOMO as a motivator for participation in virtual running events and its impact on runners’ subjective experiences. Through in-depth interviews with 19 active virtual runners and thematic analysis, the study revealed that FOMO operates through an iterative cycle: exposure to running content on social media, social anxiety, event registration, result sharing, and social validation. The findings showed that 73% of participants were initially motivated by FOMO, with manifestations such as indirect competition on digital platforms (Strava, Garmin Connect) and collection of virtual medals as a status symbol. However, the study also identified ambivalent impacts - on the one hand, increasing sport engagement, on the other hand, potentially causing emotional exhaustion when participation is driven by social pressure rather than intrinsic motivation. This study makes an important contribution to understanding the psychological dynamics of virtual sport and recommends a more balanced approach in designing virtual running events, taking into account the mental health aspects of participants.